(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Fibroids are muscular tumours, the most common benign tumours in females and typically found during the middle and later reproductive years. It originate from the smooth muscle layer of the uterus. Another medical term is leiomyoma or just myoma. It can be as small as an apple seed or as big as a melon. In unusual cases they can become very large. With the advent of high frequency ultrasonography and magnetic resonance imaging it is now possible to diagnose such cases at an early stage1. Asymptomatic uterine fibroids often left untreated. Giant fibroids are the fibroids weighing 11.4kg2,3 or more. Such a fibroid may appear as a solitary tumor or as a conglomerate mass of uterine fibroids presenting as a single uterine tumor4. Giant uterine fibroid are very rare neoplasm and represents a great diagnosis and therapeutic challange. This article illustrates a case of 34 years old woman presented with a four year history of slowly increasing abdominal size with rapid increase in the last one year associated with shortness of breath and severe anaemia by a painless lump. Total abdominal hysterectomy was performed; histologically the specimen was 9.5 kg benign uterine leiomyoma. The patients postoperative evaluation was uneventful and she went back abroad in two months time following operation. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 27-30